Real-Time Systems The International Journal of Time-Critical Computing Systems - Abdelzaher, Tarek F.; Buttazzo, Giorgio; Ramamritham, Krithi; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Real-time systems are defined as those systems in which the correctness of the system depends not only on the logical result of computations, but also on the time at which the results are produced. The journal Real-Time Systems publishes papers that concentrate on real-time computing principles and applications, which may be research papers, invited papers, project reports and case studies, standards and corresponding proposals for general discussion, and a partitioned tutorial on real-time systems as a continuing series. RTS also publishes short papers for fast publication of new high-quality ideas and correspondence articles that identify (and correct) significant errors found in published papers. Much of the work in building sophisticated, modern real-time systems is interdisciplinary in nature and is often found scattered throughout the primary literature. Real-Time Systems provides a single-source coverage of the state of the art in this exciting and expanding field. The editorial board, the writers and the readers of the journal are drawn from all parts of the world, from industry, and from academia. Papers published in Real-Time Systems cover, among others, the following topics: requirements engineering, specification and verification techniques, design methods and tools, programming languages, operating systems, scheduling algorithms, architecture, hardware and interfacing, dependability and safety, distributed and other novel architectures, wired and wireless communications, wireless sensor systems, distributed databases, artificial intelligence techniques, expert systems, and application case studies. Applications are found in command and control systems, process control, automated manufacturing, flight control, avionics, space avionics and defense systems, shipborne systems, vision and robotics, pervasive and ubiquitous computing, and in an abundance of embedded systems. The journal will also consider: Short Papers. These articles represent a means for fast publication of new, high-quality ideas in the form of short, critically refereed, technical papers. Submissions are welcomed on any topic in real-time systems, especially, but not limited to: novel techniques for the implementation of standard algorithms; significant improvements to existing well-known approaches; comparative evaluations of existing approaches; well-formed lucid critiques of standards. Correspondence Articles. These articles identify (and correct) significant errors found in published papers. Please refer to Real-Time System's Springer homepage for Instructions for Authors www.springer.com/journal/11241.
Keywords: Computer software -- Reusability; Computer organization; Special purpose computers; Control engineering; Robotics; Mechatronics; Electrical engineering; Computer Systems Organization and Communication Networks; Communications Engineering, Networks; Special Purpose and Application-Based Systems; Performance and Reliability; Control, Robotics, Mechatronics